Moss and Adams heart disease in infants, children, and adolescents : including the fetus and young adult. Volume II - Allen, Hugh D. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
"Established since 1968 as a classic pediatric cardiology text, this edition uses new technology to bring the most sought after information in the most concise, effective manner. This eighth edition is reduced from the two-volume work into a concise, easy-to-use single volume moving all but key references to the online component. Leading international experts describe state-of-the-art diagnostic and interventional techniques for treatment of young patients with congenital and acquired heart diseases and for adult survivors of congenital heart disease"--
section I. Structure and function of the cardiovascular system -- section II. Diagnostic and therapeutic methods -- section III. Electrophysiology -- section IV. Pediatric cardiac intensive care -- section V. From the gene to the neonate -- section VI. Congenital cardiovascular malformations -- section VII. Diseases of the endocardium, myocardium, and pericardium -- section VIII. Pulmonary vascular disease -- section IX. The young adult with congenital heart disease -- section X. Other special problems and issues.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2014. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Heart -- Diseases; Pediatric cardiology; Electronic books